Raw power: punk, DIY and underground cultures as spaces of resistance in contemporary Portugal - Guerra, Paula (2018)
This article focuses on presenting, analysing and understanding the do-it-yourself (DIY) representations of over 200 participants in Portuguese punk music scenes between 1977 and 2014. Through an ethnographic study of punk and the DIY ethos in Portugal, the article depicts its local interpretation and significance, and highlights the singularities of this socio-historical context. Our approach has three focal points: (1) the importance of DIY punk manifestations in the development of youth (sub)cultures, including forms of production and consumption of music, fashion, aesthetics, leisure, the night and cosmopolitanism; (2) the singularity of DIY punk manifestations in Portugal and related resistance practices in their correlation with social, political and economic development in a country outside the Anglo-Saxon context; and (3) the embedding of a DIY ethos and the associated claim to authenticity in the professions and careers in which punks engage today.